An integrative review of research evaluating organisational culture in residential aged care facilities - Kate Churruca; Emma Falkland; Maree Saba; Louise A Ellis; Jeffrey Braithwaite (BMC, 2023)
Abstract Background Evidence suggests that the culture of healthcare organisations, including residential aged care facilities (RACFs), is linked to the quality of care offered. The number of people living in RACFs has increased globally, and in turn, attention has been placed on care quality. This review aimed to identify how organisational culture is studied, sought to elucidate the results of previous studies, and aimed to establish what interventions are being used to improve organisational culture in RACFs. Methods We employed an integrative review design to provide a comprehensive understanding of organisational culture. Five academic data bases were searched (Ovid Medline, Scopus, PsycInfo, CINAHL, Embase). Articles were included if they were empirical studies, published in peer reviewed journals in English, conducted in a RACF setting, and were focused on organisational culture/climate. Results Ninety-two articles were included. Fifty-nine studies (64.1%) utilised a quantitative approach, while 24 (26.0%) were qualitative, and nine used mixed methods (9.8%). Twenty-two (23.9%) aimed to describe the culture within RACFs, while 65 (70.7%) attempted to understand the relationship between culture and other variables, demonstrating mixed and indeterminate associations. Only five (5.4%) evaluated an intervention. Conclusions This review highlights the heterogenous nature of this research area, whereby differences in how culture is demarcated, conceptualised, and operationalised, has likely contributed to mixed findings. Future research which is underpinned by a sound theoretical basis is needed to increase the availability of empirical evidence on which culture change interventions can be based.